2021 annual report on education spending in England - Christine Farquharson; Luke Sibieta; Imran Tahir; Ben Waltman (Institute for Fiscal Studies (IFS), 2021)
Education spending is the second-largest element of public service spending in the UK behind health, representing about 99 billion in 2020-21 in today's prices or about 4.5% of national income. To make efficient and equitable policy choices, it is crucial to have a clear, consistent picture of the level of spending at each phase of education, how this has changed over time, how it is likely to evolve going forwards and what factors have driven these changes. This provides policymakers and the public with a sense of current resource priorities and future challenges. These issues are also a vital component of the education policy debate, particularly given empirical evidence showing how investments at different stages of the life cycle combine to drive long-run outcomes (Cunha, Heckman and Schennach, 2010; Johnson and Jackson, 2019).
Keywords: 330; Bildungsfinanzierung; England; Großbritannien